PENGEMBANGAN MEDIA EVALUASI PEMBELAJARAN SEJARAH BERBASIS GOOGLE FORMULIR DI SMA N 1 PRAMBANAN - Dwi Purwati; Alifi Nur Prasetia Nugroho (ISTORIA: Jurnal Pendidikan dan Sejarah, 2018)
The research aimed to find out: (1) to produce history evaluation media based on google form; (2) know the level the effectiveness of google form as a evaluation teaching history in SMA N 1 Prambanan. This research use research and development method which adapted with the design development ADDIE; (1) analysis model; (2) design model; (3) development; (4) implementation; and (5) evaluation. The study population was high school in SMA N 1 Prambanan. The instruments that used to collect the data were observation sheets, interview and test achievement. The research result showed that History media evaluation based on Google Form in History with feasibility level according to the assessment by material experts was obtained by 79,8% which was category of feasible, assessment by media experts was obtained by 78,5% which was category of feasible, and assessment by learning experts was obtained by 86,3% which was category of very feasible. The limited trial result obtained percentage by 86,3% which was category of very feasible. The result of extensive trial obtained percentage by 83,6% which was category of very feasible. Keyword: Google form, media evaluation, history